Fired hollow clay bricks manufactured from black cotton soils and natural pozzolans in Kenya. (15th June 2017) - Zhang, Peiping; Huang, Jinqiu; Shen, Zhaopu; Wang, Xuelian; Luo, Feng; Zhang, Peng; Wang, Jian; Miao, Shiding
Graphical abstract: Fired hollow clay bricks have been manufactured by firing the black cotton soil and natural volcanic ashes which were both collected from Kenya. Insights on the mineralogy and firing parameters were provided in obtaining brilliant mechanical properties. Highlights: The black cotton soils and volcanic ashes are abundant in Kenya. Sintering is an attractive option to allow making use of such soils. Optimum parameters were given to get brilliant physical-mechanical properties. The mineralogy and firing behavior have been studied via various means. Products meet criterion of the first-class bricks based on GB/T 13545-2014. Abstract: The fired hollow clay bricks (FHCBs) have been manufactured by firing a type of highly expansive soils, the black cotton soil (BCS), and natural volcanic ashes (VA), which were both collected from Kenya. Characterizations including the X-ray diffraction, thermogravimetric analyses and electron microscopy have been performed to derive mineralogical transformations in the firing process. Various feedings and firing temperatures have been tried to examine impacts on the physical-mechanical properties (compressive strength, bulk density, linear shrinkage and apparent porosity). Results indicated that the mass ratio of BCS:VA 7:3–8:2 can readily diminish the shrinkage of the FHCB, and the firing temperature (1000–1100 °C) affords the best physical-mechanical performance. The products meet requirements of the first-class FHCBs MU10.0 referring to GB/T 13545-2014. The mineralogical study indicates that clay minerals in BCS undergo decomposition at about 900 °C, and the reaction as well as the phase transformation was proposed as: phyllosilicates + volcanic glass → feldspar → pyroxene → melted substances → vitreous solids, which was a reverse geology evolution of volcanic lava. This research provides a strategy in making use of vast resources BCS in Kenya obtained from municipal constructions.